Decimal money - Cherry, Richard R. (Statistical and Social Inquiry Society of Ireland, 1888)
Nearly every civilized country has already adopted decimalisation, and it is strange to say, that the United Kingdom, and some of its colonies and dependencies, enjoy, with the Ottoman Empire, the proud distinction of being the only civilized countries that have not yet done so. Still we appear at the present moment to be just as far as ever from any chance of its being adopted. I do not think that the great majority of educated persons in this country really understand the advantages of the decimal coinage, although they freely admit that it is superior to our cumbrous and complicated monetary system. If they did, they would not tolerate so long as they have done, the delay in adopting it; nor would they, as many do, consider the slight and temporary inconvenience which would be caused by the change, any hindrance to its being adopted.
Read Tuesday, 5th June, 1888
Keywords: Decimalisation; British currency; 314.15